The ethnic tensions between the Edomites and the Israelites in Obadiah - Farisani, Elelwani (Journal for semitics, 2010)
This paper examines the ethnic tensions between the Edomites and the Israelites in the book of Obadiah. The paper has three related parts. The first discusses the authorship and date of the book of Obadiah. Secondly, the paper analyses the ethnic animosity between the Israelites and the Edomites. Lastly, the paper examines how theology in general, and the Obadiah text in particular, could assist or hinder us in addressing the ethnic problem in Africa.